SISTEM INFORMASI PEMASARAN BERBASIS WEB PADA PERUMAHAN GOLD LAND ESTATE - Purnama, Fery (FORTECH (Journal of Information Technology), 2018)
The success of a business whether it be a company or an individual is reflected in the profit generated within one operational year. Profit requires businesses to have a social responsibility to their business environment. It is today that very rapid technological developments require business owners to make it even more advanced by delivering accurate information. Due to the lack of information delivery to the public regarding the marketing of housing / property with only banner and mouth-mouth information is less effective, therefore, the businessmen and residential goldland estate begin to look for other methods that can be more effective in terms of attracting enthusiasts. One of the problem solving proposals that can solve the above problem is the use of Information Technology, in this case the internet media. Web Based Marketing Information System In Gold Land Estate Housing is made with PHP web programming language with phpmyadmin database. With this application is expected to provide more complete information to the public.